Pengaruh Motivasi dan Sikap terhadap Prestasi Berwirausaha pada Mahasiswa Kampus Ciputra Makassar - Jerry; Adityavarna, Syaputra; Yauw, Shayne; Mustikarini, Carolina (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the influence of motivation and attitude on the entrepreneurial achievement of students at Ciputra Makassar Campus. Achievement motivation and risk-taking attitude are psychological factors that contribute to entrepreneurial success. This research employs a quantitative method with a sample of 100 students from various disciplines at Ciputra Makassar Campus. The data analysis technique uses Partial Least Square (PLS) with the aid of SmartPLS 4.0 software. The findings indicate that motivation does not have a direct significant effect on entrepreneurial achievement. However, motivation has a positive and significant effect on attitude, which ultimately impacts entrepreneurial achievement. Attitude is proven to be a key factor contributing to students' entrepreneurial success. Therefore, strengthening programs that enhance students' positive attitudes toward entrepreneurship is necessary to achieve optimal results.